2023
DOI: 10.3390/biochem3010004
|View full text |Cite
|
Sign up to set email alerts
|

The Cross-Talk between Microbiome and Metabolome in Rheumatoid Arthritis

Abstract: Modern “omics” sciences, including metabolomics and microbiomics, are currently being applied to inflammatory autoimmune diseases, such as rheumatoid arthritis (RA), to investigate the interplay between microbiota, metabolic function, and the immune system. In recent decades, robust evidence has suggested that disruption of the normal composition of the microbiome, known as dysbiosis, in the gut and mouth of RA patients contributes to immune dysregulation and alterations in the metabolic pathways, shaping the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…It was just recently suggested that some oral and gut microbial species (e.g., Porphy-romonas gingivalis, Prevotella copri) may also contribute to RA pathogenesis [26]. Intestinal microbiota dysbiosis occurs in the preclinical stage of RA and is closely associated with the onset of arthritis [27]. Immune dysregulation and changes in metabolic pathways play a central role regarding RA risk and progression.…”
Section: Pathophysiology Of Ramentioning
confidence: 99%
“…It was just recently suggested that some oral and gut microbial species (e.g., Porphy-romonas gingivalis, Prevotella copri) may also contribute to RA pathogenesis [26]. Intestinal microbiota dysbiosis occurs in the preclinical stage of RA and is closely associated with the onset of arthritis [27]. Immune dysregulation and changes in metabolic pathways play a central role regarding RA risk and progression.…”
Section: Pathophysiology Of Ramentioning
confidence: 99%